Effects of ambient particulate matter on vascular tissue: a review. (16th November 2020) - Shkirkova, Kristina; Lamorie-Foote, Krista; Connor, Michelle; Patel, Arati; Barisano, Giuseppe; Baertsch, Hans; Liu, Qinghai; Morgan, Todd E.; Sioutas, Constantinos; Mack, William J.
ABSTRACT: Fine and ultra-fine particulate matter (PM) are major constituents of urban air pollution and recognized risk factors for cardiovascular diseases. This review examined the effects of PM exposure on vascular tissue. Specific mechanisms by which PM affects the vasculature include inflammation, oxidative stress, actions on vascular tone and vasomotor responses, as well as atherosclerotic plaque formation. Further, there appears to be a greater PM exposure effect on susceptible individuals with pre-existing cardiovascular conditions.